2019
DOI: 10.3390/ijms20082036
|View full text |Cite
|
Sign up to set email alerts
|

Role of Dusp6 Phosphatase as a Tumor Suppressor in Non-Small Cell Lung Cancer

Abstract: DUSP6/MKP3 is a dual-specific phosphatase that regulates extracellular regulated kinase ERK1/2 and ERK5 activity, with an increasingly recognized role as tumor suppressor. In silico studies from Gene expression Omnibus (GEO) and Cancer Genome atlas (TCGA) databases reveal poor prognosis in those Non-small cell lung cancer (NSCLC) patients with low expression levels of DUSP6. In agreement with these data, here we show that DUSP6 plays a major role in the regulation of cell migration, motility and tumor growth. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 37 publications
2
12
0
Order By: Relevance
“…Multiple reports have shown that dual-specificity phosphatase 6 (Dusp6), an ERK phosphatase, attenuates ERK signaling by the dephosphorylation of ERK. 10,11 Consistent with these studies, DUSP6 has been found to be downregulated in clinical lung tissues. 12 However, how the expression of DUSP6 is regulated remains unknown.…”
Section: Introductionsupporting
confidence: 56%
“…Multiple reports have shown that dual-specificity phosphatase 6 (Dusp6), an ERK phosphatase, attenuates ERK signaling by the dephosphorylation of ERK. 10,11 Consistent with these studies, DUSP6 has been found to be downregulated in clinical lung tissues. 12 However, how the expression of DUSP6 is regulated remains unknown.…”
Section: Introductionsupporting
confidence: 56%
“…The ratio of albumin-to-fibrinogen has been used as a biomarker to judge the clinical prognosis of patients with NSCLS ( 25 ). Studies have reported that the ERK1 signaling pathway plays a key role in promoting the proliferation of NSCLC mesenchymal stem cells ( 26 , 27 ). As such, blocking the ERK signaling pathway improves the therapeutic response of patients with NSCLC to EGFR inhibitors ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been shown that ERK5 was an essential target of DUSP6 in the H460 NSCLC cell line. Downregulation of DUSP6 enhanced ERK5 activation and EMT, and forced expression of DUSP6 decreased ERK5 activation and EMT characteristics of NSCLC cells, accompanied with respective changes in cell morphology, migration, and adhesion to the extracellular matrix (ECM) [ 60 ].…”
Section: Mechanisms Of Emt Regulated By Erk5mentioning
confidence: 99%